Exploratory study of big data awareness: case of STML Students in UUM - Ooi, Hui Lin; Mohamed Udin, Zulkifli (Universiti Utara Malaysia, 2020)
In this research, researchers highlighted the level of awareness of Big Data amongst the STML undergraduate students, and factors that influence the Big Data implementation. Besides, the researcher also highlighted the level of effectiveness of Big Data towards academic performance. Overall of the research problem that had been investigated in this study are the benefits of big data and challenges on education amongst STML students in the UUM. In this research, the researcher employed quantitative research, which utilized the online questionnaire survey form to gather information from respondents. The statistical software, which is SPSS version 25 was used to analyze the data. Based on the result, it showed that the STML students have awareness and ready for big data implementation and technology. Finally, for future development, researchers should investigate the broader scope of Big Data application and implementation in education.